Delivery of encapsulated green fluorescent protein plasmid and mRNA to human embryonic kidney cells using aqueous partitioning capsules - Innes, Shelby (Kansas State University, 2023)
Aqueous Partitioning Capsules (APC) are a novel delivery system generated from peptides with a primary sequence of Ac-KKKFLIVIKKK-COHN₂. Transmission electron microscopy of APC revealed that the peptides formed a spherical shape at a pH of 2. Therefore, the peptide (Ac-KKKFLIVIKKK-COHN₂), at a pH of 2, was considered as a possible mRNA delivery system. Circular dichroism data shows that the peptides form random coils at pH 2 and 7, and forms [beta]-sheets at pH 12. The size characteristics of APC were determined using dynamic light scattering (DLS) and nanoparticle tracking analysis. APC have been shown to encapsulate rhodamine 6G dye and genetic materials, such as green fluorescent protein (GFP) plasmid and mRNA. GFP-encoding mRNA and plasmid were encapsulated, as well as attached to the outside of APC. To determine the location of the genetic materials, RiboGreen™ assays and nuclease digestion studies were used to confirm the location of the genetic material, on either the outside (accessible) or the inside (protected) of APC. APC have shown efficiency in delivering GFP plasmids and GFP mRNA for transfection of human embryonic kidney (HEK) cells. The stability of APC were studied over time using DLS to measure any size changes. Preliminary studies of APC encapsulation abilities, stability over time, and delivery of GFP mRNA and plasmid to HEK cells will be discussed.
Keywords: Nanotechnology; APC; Peptide capsules; Gene delivery